Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/lary.24877
|View full text |Cite
|
Sign up to set email alerts
|

Cervical internal carotid Artery pseudoaneurysm complicating malignant otitis externa: First case report

Abstract: Pseudoaneurysm of the internal carotid artery (ICA) is a rare complication of head and neck infections. To date, three cases of petrous ICA pseudoaneurysm have been described as a complication of otogenic infection, including only one secondary to malignant otitis externa. We present here the first case of cervical ICA pseudoaneurysm as a complication of malignant otitis externa, and stress the importance of timely diagnosis to avoid fatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…Cervical-petrous internal carotid artery pseudoaneurysms can arise from different aetiologies including congenital, trauma, malignancy, radiation therapy, and infection. Cases of ruptured ICA pseudoaneurysm due to otogenic infection are rare with only four cases reported [1][2][3][4] ; these cases were MOE complicated by pseudoaneurysm on only one ICA segment. This is the first reported case of pseudoaneurysm occurring on multiple segments of the ICA with rupture due to MOE, and demonstrates the features that predict development of complex vascular complications of unresolved otogenic infection, the timing of appropriate imaging modalities, and appropriate algorithm and duration of treatments to prevent or rescue a fatal carotid blowout.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Cervical-petrous internal carotid artery pseudoaneurysms can arise from different aetiologies including congenital, trauma, malignancy, radiation therapy, and infection. Cases of ruptured ICA pseudoaneurysm due to otogenic infection are rare with only four cases reported [1][2][3][4] ; these cases were MOE complicated by pseudoaneurysm on only one ICA segment. This is the first reported case of pseudoaneurysm occurring on multiple segments of the ICA with rupture due to MOE, and demonstrates the features that predict development of complex vascular complications of unresolved otogenic infection, the timing of appropriate imaging modalities, and appropriate algorithm and duration of treatments to prevent or rescue a fatal carotid blowout.…”
Section: Discussionmentioning
confidence: 96%
“…Pseudomonas aeruginosa is the most common causative organism. 1 Conventionally, MOE is classified according to the structural involvement CASE REPORT (Table). 5 In stage II MOE, complications can arise as it invades the temporal bone and surrounding nerve and vascular structures causing multiple cranial nerve palsies and carotid pseudoaneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To direct treatment strategies for cranial nerve palsy due to PAs in the future, we conducted a literature review of previously reported cases 6,7,[9][10][11][12][13][14][15][16]19,20,[24][25] . We searched for all reported case studies and clinical research papers regarding PAs that were published in English.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…In recent years, an increasing number of treatments for PA, such as use of a flow diverter 9,13,14 , have been reported; however, revascularization surgery remains an important strategy 10,15 . Many PA patients are difficult to treat intravascularly, particularly those with infectious diseases 6,16 , ruptures 17 , and pseudoaneurysm 16 . Furthermore, not all treatment strategies are available for all patients as some patients are allergic to contrast agents or metals 18 and some have renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%